PENCIPTAAN MUSIK KERONCONG DAN WAYANG INOVATIF DALAM PERTUNJUKAN CONGWAYNDUT - Romadona, Eko Aprianto (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
Congwayndut is one of the puppet groups whose performances depart from the traditional wayang (puppetry) style. The wayang play itself belongs to the comedy genre. Nevertheless, the stories presented are still adopted from the stories of Ramayana and Mahabarata. There are some interesting things to be used as discourse materials from Congwayndut, whose accompaniment belongs to the so-called keroncong music, while the duration of the music is shortened to two or three hours. The sanggit of the Ramayana and Mahabarata puppet stories are also interpreted humorouslyand “exibly. This paper reveals the musical facts in the puppet group, that keroncong music is able to give its own impression as pakeliran music. Then, the celloin keroncong music is able to provide a distinctive aesthetic touch toaccompany the war scene. Besides that, it also discussed the performance sketches of the Congwayndut group.Keywords: congwayndut, wayang keroncong, innovative shadow puppet.